2012
DOI: 10.1007/s12282-012-0334-5
|View full text |Cite
|
Sign up to set email alerts
|

The thrombin inhibitor, argatroban, inhibits breast cancer metastasis to bone

Abstract: Thrombin not only enhances VEGF secretion but also has a positive feedback mechanism to reexpress TF. These results indicate that inhibition of thrombin is of great value in suppression of tumor metastasis. Argatroban is a noteworthy and useful thrombin inhibitor because it has already been used in the clinical setting and has antimetastatic effects in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Although the mechanisms of intestinal radiation protection by Solulin require further investigation, Solulin's thrombin-inhibiting properties likely play a significant role in this regard, as we have shown previously that the thrombin inhibitor hirudin attenuates structural and molecular aspects of intestinal radiation injury (13). Moreover, thrombin inhibition is also known to suppress cancer cell growth (58); therefore, Solulin would be expected to reduce rather than enhance cancer growth, thereby increasing the therapeutic ratio of radiotherapy. A phase I trial of Solulin showed excellent overall tolerability (in dose ranges of 0.6–30 mg for single or multiple dose; 1–10 mg once daily for five days) with no bleeding risk, linear pharmacokinetics, dose-dependent thrombin inhibition and long plasma half-life (15–30 h) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms of intestinal radiation protection by Solulin require further investigation, Solulin's thrombin-inhibiting properties likely play a significant role in this regard, as we have shown previously that the thrombin inhibitor hirudin attenuates structural and molecular aspects of intestinal radiation injury (13). Moreover, thrombin inhibition is also known to suppress cancer cell growth (58); therefore, Solulin would be expected to reduce rather than enhance cancer growth, thereby increasing the therapeutic ratio of radiotherapy. A phase I trial of Solulin showed excellent overall tolerability (in dose ranges of 0.6–30 mg for single or multiple dose; 1–10 mg once daily for five days) with no bleeding risk, linear pharmacokinetics, dose-dependent thrombin inhibition and long plasma half-life (15–30 h) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin-mediated PAR activation has been implicated in vascular smooth muscle cell migration and proliferation as causative processes in restenosis after stent placement [44], and in tumor metastasis, where a simultaneous requirement for PARs and fibrinogen was found [45]. Thrombosis and cancer have since long been recognized as interconnected pathologies, and in this light argatroban, the tight-binding competitive inhibitor of active thrombin, has been re-evaluated as a clinically useful antiproliferative and antimetastatic agent [46]. …”
Section: Regulation Of Physiological Processesmentioning
confidence: 99%
“…However, heparin is extremely sensitive to induce thrombocytopenia and thrombosis, so it is necessary to find a new anticoagulant to overcome the shortcomings of heparin. Argatroban (AG), a small‐molecule derivative of arginine, inhibits thrombin activation directly with reliable and predictable anticoagulant actions, which has already been used in the clinical setting as thrombin inhibitor . AG can substitute heparin in patients in whom the use of heparin is contraindicated, because it can treat heparin‐induced thrombocytopenia effectively .…”
Section: Introductionmentioning
confidence: 99%
“…Argatroban (AG), a small-molecule derivative of arginine, inhibits thrombin activation directly with reliable and predictable anticoagulant actions, which has already been used in the clinical setting as thrombin inhibitor. 43 AG can substitute heparin in patients in whom the use of heparin is contraindicated, because it can treat heparin-induced thrombocytopenia effectively. 44 By comparison with traditional anticoagulants such as heparin and warfarin, AG is a more potent inhibitor of bound thrombin than heparin or low molecular weight heparins, and the mechanism action of AG is less complex than that of warfarin.…”
Section: Introductionmentioning
confidence: 99%